In vitro Study of Lactobacillus paracasei CNCM I-1518 in Healthy and Clostridioides difficile Colonized Elderly Gut Microbiota - Fehlbaum, Sophie; Chassard, Christophe; Schwab, Clarissa; Voolaid, Maarja; Fourmestraux, Candice; Derrien, Muriel; Lacroix, Christophe (Frontiers in Nutrition, 2019)
Consumption of probiotic bacteria can result in a transient colonization of the human gut and thereby in potential interactions with the commensal microbiota. In this study, we used novel PolyFermS continuous fermentation models to investigate interactions of the candidate probiotic strain Lactobacillus paracasei CNCM I-1518 (L. paracasei) with colonic microbiota from healthy elderly subjects using 16S rRNA gene amplicon sequencing and metatranscriptomics, or with microbiota in vitro-colonized with Clostridium difficile (C. difficile NCTC 13307 and C. difficile DSM 1296) – an enteropathogen prevalent in the elderly population. Small changes in microbiota composition were detected upon daily addition of L. paracasei, including increased abundances of closely related genera Lactobacillus and Enterococcus, and of the butyrate producer Faecalibacterium. Microbiota gene expression was also modulated by L. paracasei with distinct response of the Faecalibacterium transcriptome and an increase in carbohydrate utilization. However, no inhibitory effect of L. paracasei was observed on C. difficile colonization in the intestinal models under the tested conditions. Our data suggest that, in the in vitro experimental conditions tested and independent of the host, L. paracasei has modulatory effects on both the composition and function of elderly gut microbiota without affecting C. difficile growth and toxin production.